Annual report 1984: Group of Thirty - Group of Thirty (New York : Consultative Group on International and Monetary Affairs, Inc., 1984)
The publication deals with such issues as the functioning o the foreign exchange system, international banking and debt, Euro-currency markets and methods of financing the International Monetary Fund
osc 16/08/2019
Ref
Keywords: Annual Reports